Adsorção de ânions presente em efluente usando pó da casca de coco verde modificado - Lima, Ari Clecius Alves de (2009)
Its very known that the increase from residues production particularly the agricultural waste becomes an environmental problem of final destiny of this material In recent years the use of agricultural by-products for the removal of inorganic polutant from wastewater has attracted so many researchers because they are cheap simple and of low cost as sorbents natural for wastewater treatment In this work the powder of the peel of green coconut was modified chemically for the removal anions from aqueous effluent by batch process The preparation of the material modified with quaternary salt of ammonium (2-hidroxypropyltrimethyl ammonium chloride) it was accomplished through factorial experiment The chemical and physical characterization of the raw material and modified was carried out to prove the accomplished chemical modification The parameters such as pH initial anion concentration adsorbent dosage adsorption kinetic and isotherm adsorption with modified material were investigated in this study Adsorption kinetic was also examined in terms of three kinetic models ie pseudo-first-order pseudo-second-order and intraparticle diffusion model Pseudo-second-order kinetic model showed a good agreement with the experimental data. Equilibrium data were evaluated by using nonlinear and linear models of Langmuir Freundlich SIPS Redlich-Peterson Toth e Tempkin equations It was obtained that experimental data conforms to the Langmuir and Freundlich equations In order to characterize synthesized material were measurement performed of FTIR elemental analysis SEM and X-ray From FTIR analysis observed that coconut shells species may interact with NH2 groups coconut shells and the results indicated that coconut shells exhibited potential for application in removal of nitrate sulfate and phosphate from aqueous solutions.